2010
DOI: 10.1007/s12040-010-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Active and break spells of the Indian summer monsoon

Abstract: In this paper, we suggest criteria for the identification of active and break events of the Indian summer monsoon on the basis of recently derived high resolution daily gridded rainfall dataset over India . Active and break events are defined as periods during the peak monsoon months of July and August, in which the normalized anomaly of the rainfall over a critical area, called the monsoon core zone exceeds 1 or is less than −1.0 respectively, provided the criterion is satisfied for at least three consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
499
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 587 publications
(524 citation statements)
references
References 36 publications
(51 reference statements)
21
499
3
1
Order By: Relevance
“…Therefore, composites of winds and OLR for the BNFA cases were based on the seven events. While here we use an OLR index to identify active and break spells of Indian monsoon, they could also be identified by using a variety of other indices, such as a rainfall averaged over the monsoon trough zone (Rajeevan et al 2010) and a zonal wind index over Bay of Bengal south of the monsoon trough (Goswami and Ajaya Mohan 2001). It is found that breaks identified by the OLR index used here follow very closely those identified by the monsoon trough zone precipitation index (Rajeevan et al 2010).…”
Section: Methodsmentioning
confidence: 88%
“…Therefore, composites of winds and OLR for the BNFA cases were based on the seven events. While here we use an OLR index to identify active and break spells of Indian monsoon, they could also be identified by using a variety of other indices, such as a rainfall averaged over the monsoon trough zone (Rajeevan et al 2010) and a zonal wind index over Bay of Bengal south of the monsoon trough (Goswami and Ajaya Mohan 2001). It is found that breaks identified by the OLR index used here follow very closely those identified by the monsoon trough zone precipitation index (Rajeevan et al 2010).…”
Section: Methodsmentioning
confidence: 88%
“…Several studies have shown that during the southwest monsoon season (June to September) a substantial component of the variability of convection and rainfall over the Indian region arises from the fluctuation on the intraseasonal scale between active and weak or break spells (Ramamurthy, 1969;Goswami, 2005;Waliser, 2006;Rajeevan et al, 2010). Long intense breaks are known to have an impact on the seasonal monsoon rainfall over the country (Webster et al, 1998;Gadgil and Joseph, 2003).…”
Section: Intra-seasonal Variations Of the Nemrmentioning
confidence: 99%
“…Within the broad range of 10-90 day periods, two period ranges with periodicities between 10 and 20 days and 30 and 60 days respectively are particularly prominent (Goswami, 2005). Active and break spells and intraseasonal variations of the Indian summer monsoon have been extensively studied, particularly in the last decade (Yasunari, 1979;Krishnamurti and Ardanuy, 1980;Sikka and Gadgil, 1980;Webster et al, 1998;Krishnamurthy and Shukla, 2000;Annamalai and Slingo, 2001;Goswami and Ajayamohan, 2001;Lawrence and Webster, 2001;Rajeevan et al, 2010;Kulkarni et al, 2011 and the recent reviews by Goswami, 2005 andWaliser, 2006 and the references therein).…”
Section: Intra-seasonal Variations Of the Nemrmentioning
confidence: 99%
“…Prasad and Hayashi (2005) defined the onset and withdrawal of the Indian summer monsoon in terms of zonal asymmetric temperature anomaly and vertical wind shear between 850 and 200 hPa respectively. The active (periods of high rainfall) and break (periods of low rainfall) phases of the monsoon are defined as periods in which the normalized anomaly of the rainfall over a critical area, called the monsoon core zone, exceeds 1.0 or is less than −1.0, respectively, provided the criterion is satisfied for at least three consecutive days (Rajeevan et al, 2010). The 'break' is a special feature that occurs in monsoon conditions (Ramamurthy, 1969).…”
Section: Monsoon: An Overviewmentioning
confidence: 99%